2011
DOI: 10.1016/j.ultrasmedbio.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Liver Contrast Enhanced Ultrasound Perfusion Imaging in the Evaluation of Chronic Hepatitis C Fibrosis: Preliminary Results

Abstract: Abstract-We wanted to determine whether liver contrast-enhanced ultrasound (CEUS)-derived peak signal intensity (PSI) and peak signal intensity/time (PIT) predict liver fibrosis in chronic hepatitis C (CHC). Fortynine patients with CHC (METAVIR classification) and 10 control subjects were included in the study. After a bolus of 2.4 mL SonoVue (Bracco Imaging, Milan, Italy) solution was injected into a peripheral vein, the right lobe of the liver containing the right portal vein was scanned in a transverse sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Compared with contrast-enhanced CT and contrast-enhanced MRI, CEUS is low cost [15,16], repeatable, safer, and can be controlled by operators in real-time during the measurements. Moreover, previous studies have demonstrated that hepatic dynamic CEUS features are correlated with severity of chronic liver diseases (CLD) [17], degree of liver fibrosis [18], and portal pressure [19,20]. In patients with cirrhosis, the occurrence of EV is a consequence of portal hypertension (PH).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with contrast-enhanced CT and contrast-enhanced MRI, CEUS is low cost [15,16], repeatable, safer, and can be controlled by operators in real-time during the measurements. Moreover, previous studies have demonstrated that hepatic dynamic CEUS features are correlated with severity of chronic liver diseases (CLD) [17], degree of liver fibrosis [18], and portal pressure [19,20]. In patients with cirrhosis, the occurrence of EV is a consequence of portal hypertension (PH).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as Sonovue does not have an accumulation property in the liver, previous studies with this agent focused on the haemodynamic evaluation; movement of microbubble in the liver, such as transit time between portal vein and hepatic vein or hepatic vein arrival time [35]. However, their results do not seem to separate different fibrosis stages; only discriminate advanced fibrosis (F3–F4) from mild fibrosis (F0–F2), probably because of the variability of the haemodynamic-based study, difficulty of the observation of dynamic microbubble or different property of microbubble.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with sulfur hexafluoride (Sonovue; Bracco, Milan, Italy) have shown the effectiveness of haemodynamic assessment of microbubbles based on time-intensity analysis to diagnose advanced stages of fibrosis, but failed to find a significant difference in the parameters between the different fibrosis grades [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Orlacchio et al [73] used time intensity curve analysis and found an AUROC of 0.88 for the distinction between F0-2 vs F3-4. Sugimoto et al [74] proposed a subjective assessment of CEUS images to identify morphologic changes of portal vein branches, reporting AUROCs of 0.96 for F1 vs F2-4 distinction, 0.97 for F1-2 vs F3-4, and 0.91 for F1-3 vs F4.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%